Empirical modeling of plasma sheet pressure and three‐dimensional force‐balanced magnetospheric magnetic field structure: 1. Observation. Issue 10 (3rd October 2013) - Wang, Chih‐Ping; Yue, Chao; Zaharia, Sorin; Xing, Xiaoyan; Lyons, Larry; Angelopoulos, Vassilis; Nagai, Tsugunobu; Lui, Tony
Abstract [1] A three‐dimensional (3‐D) magnetic field configuration in force balance with a realistic plasma pressure distribution can provide more accurate evaluation of the role of magnetic field on plasma sheet dynamics and M‐I coupling. We used Geotail and Time History of Events and Macroscale Interactions During Substorms (THEMIS) data to establish an empirical model for nightside equatorial isotropic plasma pressure to r = 30 RE for Kp = 0–5 and for solar wind dynamic pressure (PSW) = 1.5 and 3 nPa. The model pressure is used in the companion paper for modeling a 3‐D force‐balanced pressure and magnetic field equilibrium. Larger convection during higher Kp drives the plasma sheet further earthward, resulting in larger increase of pressure and pressure gradient at smaller radial distance. On the other hand, magnetosphere compression by increasing PSW enhances pressure and pressure gradient mainly in the tail plasma sheet. While both pressure and radial gradients are enhanced with increasing Kp or PSW, there is no significant azimuthal pressure variation statistically under all Kp and PSW conditions. The empirical pressures well reproduce these statistical profiles with very high correlation coefficients. Additionally, comparisons with pressure gradients computed using two simultaneous measurements from two THEMIS spacecraft show reasonable agreement. Furthermore, our model provides more accurate pressure gradients than previous empirical models. The model magnetic field distributions obtained in the companion paper from requiring force balance with these empirical pressure profiles are also found to be consistent with the magnetic field observations, indicating that our equilibria well represent realistic 3‐D pressure and magnetic field configurations.